Left ventricular long axis disturbances as predictors for thallium perfusion defects in patients with known peripheral vascular disease. Issue 3 (1st March 1998) - Henein, M Y; Anagnostopoulos, C; Das, S K; O'Sullivan, C; Underwood, S R; Gibson, D G
Abstract : Objective: To compare resting long axis echocardiography with adenosine thallium-201 emission tomography in detecting myocardial ischaemic abnormalities in patients before peripheral vascular surgery. Design: A prospective and blinded preoperative examination of resting left ventricular minor and long axes and myocardial perfusion during adenosine vasodilatation using thallium-201 emission tomography. Setting: A tertiary referral centre for cardiac and vascular disease equipped with invasive, non-invasive, and surgical facilities. Subjects: 65 patients (40 men) with significant peripheral vascular disease, mean (SD) age 63 (10) years, and 21 control subjects of similar age. Methods: Segments were classified as normal, with fixed or reversible defects according to thallium-201 myocardial perfusion tomography. Systolic long axis abnormalities were either reduced excursion and/or abnormal shortening after A2, and diastolic abnormalities either delayed onset of lengthening > 80 ms and/or reduced peak lengthening rate < 4.5 cm/s. Segmental perfusion defects were compared with the equivalent long axes; anteroseptal for septal, inferoseptal for posterior, and lateral for left side giving a total of 195 segments. Results: Systolic long axis abnormalities predicted fixed thallium defects (sensitivity 86%, specificity 87%, positive predictive value 0.78, negative predictive value 0.93, p < 0.001), and diastolic abnormalities correlated with reversible perfusion defects (sensitivity 90%, specificity 85%, positive predictive value 0.72, negative predictive value 0.95, p < 0.001). Echocardiography characteristics of the true and false positive segments were not different in the site or the extent of abnormalities. Conclusion: Systolic long axis abnormalities predict fixed and diastolic reversible thallium perfusion defects in patients with peripheral vascular disease. Ventricular long axis may thus have a value as a screening test before peripheral vascular surgery as well as providing a means of monitoring myocardial perfusion. The high negative predictive values indicate that a negative long axis study makes significant perfusion abnormalities very unlikely in patients with high pretest probability of coronary artery disease.